A review analysis of exercise training regimes among females with polycystic ovary syndrome - Rao, Mubarra; Khan, Amna Aamir; Adnan, Qurat Ul Ain (Journal of the Pakistan Medical Association, 2023)
Objective: The current systematic review was planned to provide quality assessment of different exercise regimes and their outcomes on the symptoms of polycystic ovary syndrome, and to see if one exercise regime was better than the rest. Methods: Search was conducted on PubMed and Google Scholar databases for studies published between 2001 and 2021 whose full text was available. The search yielded 28 studies that were reviewed. Results: The current evidence suggests that exercise regimes, such as high-intensity interval training, progressive resistance training, aerobic exercises, and yoga may improve polycystic ovary syndrome conditions. This is accomplished through treating associated risk factors, like body morphology, insulin resistance, hyperandrogenism, lipid profile, reproductive hormones, menstrual cycle, and quality of life. Conclusion: Exercise regimes improves several symptoms of polycystic ovary syndrome. However, selecting a specific exercise regime over others as the standardised treatment protocol remained inconclusive. Key Words: Polycystic ovarian syndrome, Exercises, High-intensity interval training, Aerobic exercises.